Distinct roles for the domains of the mitochondrial aspartate/glutamate carrier citrin in organellar localization and substrate transport - Sotiria Tavoulari; Denis Lacabanne; Gonçalo C. Pereira; Chancievan Thangaratnarajah; Martin S. King; Jiuya He; Suvagata R. Chowdhury; Lisa Tilokani; Shane M. Palmer; Julien Prudent; John E. Walker; Edmund R.S. Kunji (Elsevier, 2024)
Objective: Citrin, the mitochondrial aspartate/glutamate carrier isoform 2 (AGC2), is structurally and mechanistically the most complex SLC25 family member, because it consists of three domains and forms a homo-dimer. Each protomer has an N-terminal calcium-binding domain with EF-hands, followed by a substrate-transporting carrier domain and a C-terminal domain with an amphipathic helix. The absence or dysfunction of citrin leads to citrin deficiency, a highly prevalent pan-ethnic mitochondrial disease. Here, we aim to understand the role of different citrin domains and how they contribute to pathogenic mechanisms in citrin deficiency. Methods: We have employed structural modeling and functional reconstitution of purified proteins in proteoliposomes to assess the transport activity and calcium regulation of wild-type citrin and pathogenic variants associated with citrin deficiency. We have also developed a double knockout of citrin and aralar (AGC1), the two paralogs of the mitochondrial aspartate/glutamate carrier, in HAP1 cells to perform mitochondrial imaging and to investigate mitochondrial localisation. Results: Using 33 pathogenic variants of citrin we clarify determinants of subcellular localization and transport mechanism. We identify crucial elements of the carrier domain that are required for transport, including those involved in substrate binding, network formation and dynamics. We show that the N-terminal domain is not involved in calcium regulation of transport, as previously thought, but when mutated causes a mitochondrial import defect. Conclusions: Our work introduces a new role for the N-terminal domain of citrin and demonstrates that dysfunction of the different domains contributes to distinct pathogenic mechanisms in citrin deficiency.